QUANTITATIVE EASING OF MONETARY POLICY AND ITS MANIFESTATIONS IN THE FIXED INCOME SEGMENT - Jakl, Jakub (2019)
This dissertation thesis is devoted to the topic of Quantitative Easing (QE) of monetary policy and consists from four academic papers that deal with the quantitative easing and its manifestations, mainly in the fixed income segment, in the U.S. and the Eurozone economy.The first paper focuses on the QE episode undertaken by the Federal Reserve System in the U.S. and its effects on assets prices, mainly on QE-targeted assets and its investment alternatives using event study and VAR analysis. In this paper a non-negligible impact of QE on purchased assets was found in both models through all waves of QE and time persistency patterns in VAR impulse-response functions (IRFs) part. Furthermore, some evidence for portfolio-balance and other related effects was found.The second paper focuses on analysis of possible effects of the ECB’s Public sector purchase programme (PSPP) on portfolios of the Eurozone investors. This paper incorporates the counterfactual analysis approach and uses sectoral data regression analysis of asset holdings of different investors in the Eurozone. The series of obtained regression estimates and counterfactual analysis graphic representation identified a nonnegligible effect of the PSPP on the rebalancing of government bond portfolios towards riskier corporate bonds and equities across investor types in major Eurozone countries.The third paper focuses on the effects of the ECB's Corporate sector purchase programme (CSPP) on yields of corporate sector bonds and its impact on corporate sector debt markets. Detailed regression-controlled event study focused on relevant events and impulse-response analysis of constructed VAR models were used to obtain series of sector-specific and country-specific results. Results showed non-negligible impact of the CSPP on purchased bonds in both models.